A protocol for analysis of the quantitative characteristics of leaf pubescence in potato - A. V. Doroshkov; M. A. Genaev; D. A. Afonnikov (Вавиловский журнал генетики и селекции)
Plant leaf pubescence is one of the important features, which is responsible for microclimate formation near the epidermis. It is involved in protection against adverse biotic and abiotic environmental factors. In Solanaceae, to which belongs the potato Solanum tuberosum L., leaf pubescence appears as multicellular unbranched trichomes of diverse size and morphology. Pubescence of this plants promotes resistance to insect pests, in particular, Colorado potato beetle and aphid, which is a carrier of viral diseases. During the process of breeding and genetic experiments, there is a need to assess the intensity of leaf pubescence of potato plants. For this task, micrographs taken under a microscope are commonly used. They are used to count different types of trichomes on the leaf surface to characterize the intensity of potato leaf pubescence. This approach requires visual counting of trichomes under a microscope and is fairly laborious. This protocol describes a rapid technology for quantitative assessment of the characteristics of potato pubescence (the number of trichomes on the leaf surface and the average length of trichomes) to solve the problems of genetics and breeding of this plant. It consists of a preparation technology, digital imaging of leaf folds with an optical microscope in transmitted light and subsequent automatic processing of images using the LHDetect2 software.